Parameterization of Mangrove Root Structure of Rhizophora stylosa in Coastal Hydrodynamic Model - Mori, Nobuhito; Chang, Che-Wei; Inoue, Tomomi; Akaji, Yasuaki; Hinokidani, Ko; Baba, Shigeyuki; Takagi, Masashi; Mori, Sotaro; Koike, Hironoshin; Miyauchi, Miho; Suganuma, Ryosuke; Sabunas, Audrius; et al. (Frontiers in Built Environment, 2022)
Mangroves are able to attenuate tsunamis, storm surges, and waves. Their protective function against wave disasters is gaining increasing attention as a typical example of the green infrastructure/Eco-DRR in coastal regions. Hydrodynamic models commonly employed additional friction or a drag forcing term to represent mangrove-induced energy dissipation for simplicity. The well-known Morison-type formula (Morison et al. 1950) has been considered appropriate to model vegetation-induced resistance in which the information of the geometric properties of mangroves, including the root system, is needed. However, idealized vegetation configurations mainly were applied in the existing numerical models, and only a few field observations provided the empirical parameterization of the complex mangrove root structures. In this study, we conducted field surveys on the Iriomote Island of Okinawa, Japan, and Tarawa, Kiribati. We measured the representative parameters for the geometric properties of mangroves, Rhizophora stylosa, and their root system. By analyzing the data, significant correlations for hydrodynamic modeling were found among the key parameters such as the trunk diameter at breast height (DBH), the tree height H, the height of prop roots, and the projected areas of the root system. The temporal changes of these representative factors were also discussed in terms of the tree age. These empirical relationships are summarized for numerical modeling at the end.